Pengaruh Kualitas Audit, Profitabi litas, dan Kepemilik an Perusahaan Terhadap Penerimaan Opini Going Concern (Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia) - Hasrumi, Hasrumi; Bakry, Moh Iqbal; Jurana, Jurana (Universitas Islam Negeri Sunan Kudus, 2017)
This study aims to determine the effect of Audit Quality, Profitability, Ownership of the Company on acceptance of going concern opinion. Samples of research as many as 35 companies. Sampling method is Purposive Sampling Method. The data used are secondary data obtained from Indonesia Stock Exchange (IDX) and Indonesian Capital Market Directory (ICMD). Analytical method used is logistic regression analysis using hypothesis test that is evaluate fit model, test (Cox and Snell’s R Square), model feasibility test, parameter estimation and its interpretation. The result of this research concludes that: Audit quality has no effect to acceptance of going concern opinion . Profitabiltas significant effect on the acceptance of going concern opinion. Ownership of the company has no effect on the acceptance of going concern opinion. This research suggests: Further research should add to the observation period. Audit quality variables should be proxied for different measurement tools. The limitations of this study are the lack of books on audit quality and going concern opinion.